The Responses of a Grapevine Rhizosphere System to Mulching Using Amplicon Sequencing and Transcriptomic Analysis - Bo Wang; Xi-Cheng Wang; Zhuang-Wei Wang; Zhen-Xiao Chen; Wei-Min Wu (Agronomy, 2023)
Although mulching is a widely used agronomic practice, its effects on the rhizosphere remain poorly understood. Here, we employed amplicon and transcriptomic sequencing to investigate variations in a grapevine rhizosphere system under mulch treatment (rice straw + felt + plastic film). Analyzing 16S and intergenic spacer (ITS) rRNA sequences indicated that the Shannon and Simpson indices of the bacterial and fungal communities increased markedly under mulch treatment. The bacterial and fungal compositions varied significantly between the control and mulch treatments. Mulching enriched for potentially beneficial microbes that confer disease resistance to plants or participate in nitrogen metabolism (Kaistobacter, Ammoniphilus, Lysobacter, Ammoniphilus, Alicyclobacillus, Aquicella, Nitrospira, Chaetomium, and Microascus), whereas more potentially pathogenic microbes (Fusarium and Gibberella) were detected in the control. Moreover, certain bacteria and fungi exhibited different correlations with the root transcriptome functions of the MEBlue module. The complexity of the bacterial and fungal co-occurrence networks increased with higher node numbers, positive and negative links after mulching. Following mulching, the rhizosphere showed elevated pH, organic matter, and catalase activities, and decreased sucrase and cellulase and β-glucosidase activities. Our results provide comprehensive data showing how a grapevine rhizosphere system responded to mulching treatment and shed important insight into mulching practices for fruit trees.